1995
DOI: 10.1016/0304-3959(94)00218-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of citalopram in the treatment of fibromyalgia

Abstract: Amitriptyline and cyclobenzaprine have shown some efficacy in treatment of the generalised pain syndrome, fibromyalgia. The aim of this study was to examine the efficacy of antidepressant dosages of the serotonin re-uptake inhibitor citalopram in fibromyalgia. In a double-blind, placebo-controlled study 22 patients with fibromyalgia were randomized to treatment with citalopram for 4 weeks at a dosage of 20 mg a day while 21 received placebo. After 4 weeks the dosage was increased to 40 mg for a further 4 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(102 citation statements)
references
References 23 publications
0
98
0
4
Order By: Relevance
“…50,54,56,[97][98][99][100][101][102] Five studies comparing SSRIs with placebo have found them to be superior to placebo for relieving neuropathic pain. 50,[103][104][105][106] In fibromyalgia, fluoxetine (ES: 1.08) is reported to have greater analgesic activity than citalopram (ES: 0.45) and paroxetine (ES: 0.19).…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…50,54,56,[97][98][99][100][101][102] Five studies comparing SSRIs with placebo have found them to be superior to placebo for relieving neuropathic pain. 50,[103][104][105][106] In fibromyalgia, fluoxetine (ES: 1.08) is reported to have greater analgesic activity than citalopram (ES: 0.45) and paroxetine (ES: 0.19).…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…The recent meta-analyses of antidepressant trials have shown that tricyclic antidepressants to be moderately effective in the treatment of patients with FM (7,15). Although the studies evaluating the effects of selective serotonin reuptake inhibitors (SSRIs) in the treatment of FM yielded inconsistent results, these medications are better tolerated than the tricyclic antidepressants (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Fluoxetine hydrochloride and amitriptyline were more effective than placebo in reducing FM symptoms, and the combination of both worked better than either alone. 37 In other reports, however, there was no beneficial effect of fluoxetine 106 or of a different serotonin reuptake inhibitor, citalopram, 107 or of tenoxicam and bromazepam. 108 Treatment with alprazolam combined with ibuprofen demonstrated modest improvement.…”
Section: Can Fm Be Effectively Treated?mentioning
confidence: 97%